Barcode Scanning Conveyor Automation System for Expedition Goods - Eko Sulistyo; Ilham, Muhamad Ilham; Dhea Prameswari; Yudhi (Emitor: Jurnal Teknik Elektro, 2025)
The development of expeditionary goods separation system technology is currently increasingly leading to automation systems. Including shipping expedition goods. However, currently the process of separating goods during shipping expeditions is still mostly done manually. Therefore, research is needed to create an automatic control system tool that can separate and record expedition goods so that it becomes more effective and efficient. The methodology used is 3 GM66 Barcode Readers to read Barcodes on expedition goods from the top, left and right positions. The reading results are sent to the Arduino Mega R3 and processed to move the servo motor and separate the expedition goods into 3 different sortings according to the destination area and 1 sorting for rejected goods. Reading data from the Barcode is also sent to the WiFi module and processed to be sent to the expedition's goods database. The expedition goods database then displays the data on the IoT control system. As a result, the Barcode reading by the Barcode Reader from the top, left and right positions was read well with an error percentage of 0%. Then separate the expedition goods from the reading results separately according to the destination with an error percentage of 0%. And reading the expedition goods input data through reading the Barcode is stored in the expedition goods database and can be read again based on the Barcode, recipient's name, recipient's address, and No. Recipient's cellphone.